2021
DOI: 10.48550/arxiv.2102.12095
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synergy Between Semantic Segmentation and Image Denoising via Alternate Boosting

Abstract: The capability of image semantic segmentation may be deteriorated due to noisy input image, where image denoising prior to segmentation helps. Both image denoising and semantic segmentation have been developed significantly with the advance of deep learning. Thus, we are interested in the synergy between them by using a holistic deep model. We observe that not only denoising helps combat the drop of segmentation accuracy due to noise, but also pixel-wise semantic information boosts the capability of denoising.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…It can be observed that the noise still interferes with the deep learning model, especially for targets that are difficult to focus on with the naked eye. Therefore, some works combine semantic segmentation and image denoising to achieve high-precision semantic information classification [ 44 ]. We plan to apply related ideas to brain MRI segmentation in future work.…”
Section: Discussionmentioning
confidence: 99%
“…It can be observed that the noise still interferes with the deep learning model, especially for targets that are difficult to focus on with the naked eye. Therefore, some works combine semantic segmentation and image denoising to achieve high-precision semantic information classification [ 44 ]. We plan to apply related ideas to brain MRI segmentation in future work.…”
Section: Discussionmentioning
confidence: 99%